Archives of times past : conversations about South Africa's deep history - Kros, Cynthia; Wright, John; Buthelezi, Mbongiseni; Ludlow, Helen; Blundell, Geoffrey; Boeyens, Jan; Esterhuysen, Amanda; King, Rachel; Kriel, Lize; Lekgoathi, Sekibakiba Peter (Wits University Press, 2022)
An exploration of the archive on southern Africa's past in the pre-colonial era, bringing new ideas about source material and archiving from scholars in southern Africa and elsewhere. It focusses on the question: 'How do we know, or think we know, what happened in the times before European colonialism?'